2000
DOI: 10.1177/0145445500242006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interpersonal Patient and Therapist Behavior on Outcome in Cognitive-Behavior Therapy

Abstract: Empirical studies are reviewed, the aim being to investigate characteristics of the therapeutic relationship in cognitive-behavior therapy (CBT) and to identify therapist or patient interpersonal behavior that affects treatment outcome. CBT is characterized by a more active and directive stance on the part of the therapists and higher levels of emotional support than are found in insight-oriented psychotherapies. Therapists express high levels of empathy and unconditional positive regard, similar to those expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
2
17

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 85 publications
(180 reference statements)
3
127
2
17
Order By: Relevance
“…Although the intervention manual clearly articulated a collaborative, guided discovery approach to the real-world application of skills, mothers interviewed for this qualitative study appeared to remember, with some detail, specific advice from their facilitators, which they perceived as extremely helpful and not coercive. Cognitive-behavioral therapists are typically directive with clients, and positive treatment outcomes have been associated with clients' perception of cognitive-behavioral therapists' being active, skillful, and self-confident in sessions (Keijsers, Schaap, & Hoogduin, 2000). Although we did not analyze the sessions that were recorded for supervision, this unexpected finding is an avenue for future research.…”
Section: Discussionmentioning
confidence: 92%
“…Although the intervention manual clearly articulated a collaborative, guided discovery approach to the real-world application of skills, mothers interviewed for this qualitative study appeared to remember, with some detail, specific advice from their facilitators, which they perceived as extremely helpful and not coercive. Cognitive-behavioral therapists are typically directive with clients, and positive treatment outcomes have been associated with clients' perception of cognitive-behavioral therapists' being active, skillful, and self-confident in sessions (Keijsers, Schaap, & Hoogduin, 2000). Although we did not analyze the sessions that were recorded for supervision, this unexpected finding is an avenue for future research.…”
Section: Discussionmentioning
confidence: 92%
“…It also has been suggested that if a therapist uses too many of these directive behaviors, that this will negatively affect ratings of the counselors interpersonal skills (warmth, empathy, etc. ), however, this has not typically been found in the adult treatment literature (Keijsers, Schaap, & Hoogduin, 2000). In addition, McKay, Stoewe, McCadam, and Gonzales (1998) found that therapist active engagement strategies with families, such as explaining the helping process, actively focusing conversation onto immediate and practical concerns, and directly addressing barriers to treatment, resulted in greater family retention into treatment.…”
Section: Therapist Direct Influence Skillsmentioning
confidence: 93%
“…For behaviour therapists, their relationship is good when they are effective and influential. 67,103 This process is linked to social influence theory: 91 the ability of the therapist to influence the patient on the basis of social power. Influence is also linked to the credibility of the therapist.…”
Section: Influencementioning
confidence: 99%